The space atlas - Couper, Heather; Corbella, Luciano; Henbest, Nigel (San Diego : Harcourt Brace Jovanovich, 1992)
An overview of the planets, moons, and other bodies of the solar system, as well as distant stars, galaxies, and other celestial phenomena.
"Gulliver books.".
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Junior High School.
7.5
Keywords: Astronomy -- Juvenile literature; Astronomy; Astronomy; Outer space -- Exploration -- Juvenile literature; Solar system -- Juvenile literature; Outer space; Solar system; Outer space; Solar system